The role of library leaders in maintaining service quality during the covid-19 pandemic: A case study at the Ponorogo Muhammadiyah University Library - Ayu Wulansari; Yolan Priatna (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: The emergence of covid-19 has a big impact on the joints of human life, as well as libraries. As one of the organizations engaged in library education service visits, they are forced to “change” themselves quickly. Purpose: This change will be difficult if the library does not have a leader who is not competent in addressing this case. This study uses qualitative methods with descriptive approaches in explaining the role of the leadership in the Muhammadiyah University of Ponorogo library during the Covid-19 pandemic. Method: Data collection is obtained from literature studies that come from books, journals, or other relevant sources as well as interviews with parties deemed important. Findings: The results of this discussion show that leadership is an important figure in the changes made by the Muhammadiyah University of Ponorogo library during covid-19. This can be seen from the policies issued during the Covid-19 pandemic that protect members but do not reduce the quality (library rights) of the library. Conclusion: Remembering to be the leader of an organization one must have several skills/abilities such as technical, conceptual, and human abilities.